Behind a spoken discourse: Idiomatic expressions in IELTS speaking test (ELT Forum: Journal of English Language Teaching, 2022)
The performance of a wider range of vocabulary mastery in IELTS speaking test is imperative to escalate the band score achievement. The present study sought to investigate the teaching of idioms in an IELTS preparation program with regards to the kinds of idioms taught in the class, how the students used them during the mock post test, and whether the use of idioms interfere with the grammatical accuracy. The study was in urgency to be conducted with regards to the absence of the teaching of idioms for IELTS at least in the past five years. The data were collected from the recorded speaking performance of five students at intermediate level of English, in both mock pretest and post test to see if there were some alterations in the predicted test score and a deep interview with one candidate to have strengthen the arguments. The results showed significant differences in the students’ performance of speaking in pretest and after they were taught idioms despite some less accurate grammar in the sentence productions. The findings of the study can have potential pedagocical implications for teachers of IELTS preparation classes to incorporate the teaching of idioms in either speaking or vocabulary lessons.